Combination of selective etching and impregnation toward hollow mesoporous bioactive glass nanoparticles - Mutlu, Nurshen; Beltran, Ana Maria; Nawaz, Qaisar; Michalek, Martin; Boccaccini, Aldo R.; Zheng, Kai (Nanomaterials, 2021)
In this study, binary SiO2-CaO hollow mesoporous bioactive glass nanoparticles (HMBGNs) are prepared by combing selective etching and impregnation strategies. Spherical silica particles (SiO2 NPs) are used as hard cores to assemble cetyltrimethylammonium bromide (CTAB)/silica shells, which are later removed by selective etching to generate a hollow structure. After the removal of CTAB by calcination, the mesoporous shell of particles is formed. Calcium (Ca) is incorporated into the particles using impregnation by soaking the etched SiO2 NPs in calcium nitrate aqueous solution. The amount of incorporated Ca is tailorable by controlling the ratio of SiO2 NPs:calcium nitrate in the soaking solution. The produced HMBGNs are bioactive, as indicated by the rapid formation of hydroxyapatite on their surfaces after immersion in simulated body fluid. In a direct culture with MC3T3-E1 cells, HMBGNs were shown to exhibit concentration-dependent cytotoxicity and can stimulate osteogenic differentiation of MC3T3-E1 cells at concentrations of 1, 0.5, and 0.25 mg/mL. Our results indicate that the combination of selective etching and impregnation is a feasible approach to produce hierarchical HMBGNs. The produced hollow particles have potential in drug delivery and bone tissue regeneration applications, and should be further investigated in detailed in vitro and in vivo studies.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Alkaline etching; Bioactive glasses; Bone regeneration; Hollow mesoporous structure; Impregnation